Multikulturalisme Indonesia: Analisis Semiotik dalam Karya Lukis Kontemporer “Story of Love” Karya Abdullah Ibnu Thalhah - Bintang Dwi Saputra; Nurul Maghfiroh; Yulia Lestari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Indonesia is a country rich in cultural diversity, ethnicities, and traditions, which are essential aspects of its national identity. The traditions and natural beauty of Indonesia have become a significant part of shaping the norms and values of its people. Fine arts, particularly painting, serve as an effective medium for representing this cultural richness. Story of Love by Abdullah Ibnu Thalhah uses wayang symbols, an Indonesian cultural heritage, blended with global pop culture characters like Patrick from SpongeBob SquarePants. Through a semiotic approach, this study aims to explore the meanings within Story of Love, showcasing the interaction between local culture and elements of pop culture. This painting not only reflects Indonesia's cultural identity but also demonstrates how fine art can respond and adapt to modern influences, reinforcing multiculturalism amid global developments.